2010
DOI: 10.1016/j.ahj.2010.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of post-dilation after stent deployment in patients presenting with and without acute myocardial infarction

Abstract: Background In the practice of percutaneous coronary intervention (PCI), post-dilatation often is performed after stent deployment to improve stent expansion. However, aggressive mechanical expansion is a risk factor of distal embolization and microvascular injury, especially for patients with acute myocardial infarction (AMI). Few studies have investigated the effects of post-dilatation on medium-term clinical outcomes. Methods and Results Patients enrolled in the multicenter NHLBI Dynamic Registry between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 27 publications
0
37
1
1
Order By: Relevance
“…In terms of stent type, there Our findings reassure us that in the current era of primary PCI for STEMI, stent postdilatation is justifiable if angiographically indicated to optimise stent deployment. Nonetheless, the results of our study differed from those of a recently published study by Zhang et al [5] looking at the effects of postdilatation in patients who presented with and without AMI, between 2001 and 2006 in the NHLBI Dynamic Registry. The authors found that postdilatation was associated with an increased risk of death and repeat MI in patients who presented with AMI.…”
Section: Angiographic Outcomescontrasting
confidence: 85%
“…In terms of stent type, there Our findings reassure us that in the current era of primary PCI for STEMI, stent postdilatation is justifiable if angiographically indicated to optimise stent deployment. Nonetheless, the results of our study differed from those of a recently published study by Zhang et al [5] looking at the effects of postdilatation in patients who presented with and without AMI, between 2001 and 2006 in the NHLBI Dynamic Registry. The authors found that postdilatation was associated with an increased risk of death and repeat MI in patients who presented with AMI.…”
Section: Angiographic Outcomescontrasting
confidence: 85%
“…PD has been recommended to overcome these complications and provide optimal stent expansion in elective PCI . However, there is no consensus among interventional cardiologists regarding performance of PD during primary PCI, due to limited data and a general lack of evidence …”
Section: Discussionmentioning
confidence: 99%
“…Dilatation with a noncompliant (NC) balloon after stent deployment, to provide optimal expansion, reduced the target vessel revascularization (TVR) rate and resulted in better angiographic results and clinical outcomes in patients undergoing elective PCI . However, there is no consensus among interventional cardiologists regarding performance of postdilatation (PD) in primary PCI . In this study, we sought to evaluate the effects of PD on postprocedural angiographical and 6‐month clinical outcomes in patients who underwent primary PCI with a DES.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some reports showed that among patients with acute myocardial infarction, post-dilation was associated with a significantly higher risk of death/myocardial infarction but not associated with the risk of repeat revascularization. Whereas, among patients who did not present with acute myocardial infarction, post-dilation was not associated with risks of death/myocardial infarction or repeat revascularization[11],[12]. However, no data are currently available to clarify whether the high-pressure post-dilation has an adverse effect on short-term cardiac function in patients without acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%